Evolutionary Analyses Reveal Diverged Patterns of SQUAMOSA Promoter Binding Protein-Like (SPL) Gene Family in Oryza Genus - Zhong, Hua; Kong, Weilong; Gong, Ziyun; Fang, Xinyi; Deng, Xiaoxiao; Liu, Chang; Li, Yangsheng (Frontiers in Plant Science, 2019)
The SPL (SQUAMOSA promoter binding protein-like) gene family is one of the plant-specific transcription factor families and controls a considerable number of biological functions, including floral development, phytohormone signaling, and toxin resistance. However, the evolutionary patterns and driving forces of SPL genes in the Oryza genus are still not well-characterized. In this study, we investigated a total of 105 SPL genes from six AA genome Oryza representative species (O. barthii, O. glumipatula, O. nivara, O. rufipogon, O. glaberrima, and O. sativa). Phylogenetic and motif analyses indicated that SPL proteins could be divided into two distinct lineages (I and II), and further studies showed lineage II consisted of three clades (IIA, IIB, and IIC). We found that clade I had comparable structural features with clade IIA, whereas genes in clade IIC displayed intrinsic differences, such as lower exon numbers and the presence of miR156 regulation elements. Nineteen orthologous groups of OsSPLs in Oryza were also identified, and most exons within those genes maintained constant length, whereas length of intron changed relatively. All groups were constrained by stronger purifying selection and diversified continually including alterative gene number, intron length, and miR156 regulation. Subsequently, cis-acting element analyses revealed the potential role of SPLs in wild rice, which might participate in light-responsive, phytohormone response, and plant growth and development. Our results shed light on that different evolutionary rates and duplication events might result in divergent evolutionary patterns in each lineage of SPL genes, providing a guide in exploring diverse function in the rice gene family among six closely related Oryza species.